Genome-Based Analysis Reveals the Taxonomy and Diversity of the Family Idiomarinaceae - Liu, Yang; Lai, Qiliang; Shao, Zongze (Frontiers in Microbiology, 2018)
Idiomarinaceae is a family of Gram-stain negative, mesophilic euryhalophiles. To provide a robust framework for the evolutionary and taxonomic relationships of bacteria of this family, we compared herein the genomes of 36 type strains and 43 non-type strains using 16S rRNA gene sequences, core genome based 78 single-copy orthologous proteins, digital DNA-DNA hybridization and Average Nucleotide Identity (ANI) estimation. The 79 bacteria of this family were consistently divided into taxon I, taxon II and taxon III corresponding to the three genera Idiomarina, Pseudidiomarina and Aliidiomarina, which contained 13 putative new genospecies in addition to 35 well-defined species represented by each type strain. Furthermore, genetic diversity of this family was evident at the genus- and species levels, and exceeded that which is defined currently by the named species. In view of multiple genotypic characteristics clearly distinct from the other two genera, we propose reinstating the genus Pseudidiomarina as a monophyletic taxon. Taken together, this is the first genome-based study of the taxonomy and diversity of bacteria within the family Idiomarinaceae, and will contribute to further insights into microbial evolution and adaptation to saline environments.